Новый эпиграфический документ из Никония - Дана, М.; Бруяко, И.В.; Секерская, Н.М. (Материалы по археологии Северного Причерноморья, 2019)
The letter on the lead plate is publishing in this article. It was obtained by the illegal excavations of the ancient poleis Nikonion. The document is dated for the beginning IV cent. BC. This is the time of flourishing of Nikonion according to archaeological data. Text contains the information on a particular issue connected with the business relations. The recipient is the person involved in the production (blacksmith) who lived in Nikonion or on it vicinity. His name was Dionysios. Sender of letter was a man with name Artemidoros. Third person – Posideos through whom the money sum in 4 staters was transmitted. This money was meant for some deal. The published document is a very important addition to the epigraphic collection from Nikonia that still remains a very not numerous.